FIRM VALUE IN REGULATED MARKETS AS SEEN FROM INCOME SMOOTHING MODERATE BY MARKET RISK - Sari, Sri Mustika; Irfan, Andi (Jurnal Al-Iqtishad, 2024)
The prevalence of accounting scandals can resulting in the collapse of firms which has been attributed to the opportunistic behaviors of managers. Previous literature found that income smoothing affects firm value. A regulated market is able to minimize the practice of income smoothing. This study aims to examine the effect of income smoothing and firm value with market risk as a moderating variable. Through a purposive sampling technique, thirty-four companies with the best good corporate governance in their respective sectors (source: www.theiconomics.com) on the Indonesia Stock Exchange were selected as samples for the 2020 – 2021 period. Multiple regression was used to analyze secondary data have been collected. This study finds a negative effect of income smoothing and market risk on firm value, and market risk does not strengthen income smoothing and firm value. The results of this study have several practical and theoretical implications, companies must minimize the practice of income smoothing so that published financial reports reflect the actual condition of the company so that it can increase company value along with investor confidence to invest.